Consumer partnerships in research (CPR) checklist: A method for conducting market research with vulnerable consumers. (March 2023) - Carlini, Joan; Robertson, Julia
There is a need for better evidence on how to effectively support consumer partnerships in research (CPR). This paper aims to provide a practical checklist for market researchers to plan, implement, and report research where vulnerable consumers are the target population. A vulnerable consumer is someone who, due to their circumstances, may be disadvantaged or at risk in some marketplace situations. Here, it is proposed that research conducted about vulnerable consumers must include consumer co-researchers as partners in the research process. The involvement of consumers as co-researchers addresses this methodological gap to some extent by democratizing research design and empowering vulnerable consumers. The CPR Checklist is based on an integrative realistic review method, content validation via an expert panel, and includes consumer co-researcher involvement in the research process. Considering the complexities of vulnerable consumers and market research, the CPR Checklist provides a suite of 'how and why' questions to guide rigorous and ethical project conduct.